Assessment of relative Salty taste of Unani drugs by serial dilution method and its relation with Mizaj and Pharmacological action (Bangladesh Journal of Medical Science, 2023)
Introduction: Mizaj-e-Advia (Temperament of drug) is the central concept for drug action in traditional Unani medicine. Mizaj-e- Advia is determined by different methods, of them Qiyas (Analogy) and Tajriba (Experimentation) are the conventional one. Tajriba is applied to confirm the Mizaj-e-Advia of drugs and Qiyas is undertaken by comparison of different physico-chemical properties of drug substances with a known comparator drug. Organoleptic characters i.e.colour, taste, smell, weight, texture, etc., are the most important determinants to predict Mizaj-e- Advia in humans. Taste is considered as one of the strongest determinant in assessment of Mizaj-e- Advia. Since, they are very subjective indicators, so there is a need to assess them with an objective technique. The present study attempted to evaluate the relative saltiness of drugs with salty taste.Methodology: The taste of different salty drugs in relation to standard as prescribed in Unani system of Medicine i.e., Namak Ta’am (Sodium chloride, NaCl) was assessed by serial dilution method. The value has been expressed as a ratio with respect to NaCl. The Darjate- Mizaj (grades of temperament) of various salt tasting drugs was recorded from classical Unani literature and their correlation coefficient was calculated.Results: A positive moderate correlation was observed between the Darjat-e-Mizaj and the saltiness values of various drugs of salt taste. The observation from the data employed that there was variation in salt detection limit among various salt tasting drugs. Naushadar (Ammonium Chloride) was observed to have greater tendency to retain its saltiness value, and Namak-e-Sanbhar (Impure Sodium Chloride) was observed to have least saltiness value among the various salt tasting drugs.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 163-170